Atmospheric cold plasma technology for meat industry: A bibliometric review - M. Vukić; D. Vujadinović; M. Smiljanić; V. Gojković–Cvjetković (Теория и практика переработки мяса)
Atmospheric cold plasma is an innovative, non-thermal technology. It has shown promising results for a broad range of food processing applications. On the basis of those facts, it has prompted growing attention in the scientific community. This paper reviews the literature generation trends surrounding the atmospheric cold plasma technology. A bibliometric analysis was carried out to objectively and analytically uncover the knowledge development in the atmospheric cold plasma technology within the context of meat processing. The research began with querying the Dimensions database for scientific articles published over the past two decades. A total of 105 papers were published during this period. The articles were examined according to several bibliometric metrics such as the year of publication, countries, institutions, sources, authors, and keywords frequency. The results of the bibliometric analysis revealed that researchers are very interested in studying the interface of the atmospheric cold plasma technology and meat processing. In the last couple of years, the number of publications on the topic has been growing. This is the first bibliometric investigation of the atmospheric cold plasma technology in the context of meat processing. To the authors’ best knowledge, no similar analysis has been performed before. This paper provides researchers with a better understanding of topic developments. A better understanding can aid future research by closing present knowledge gaps. Hence, the paper provides the continuation of up-to-date technological discussions among researchers.